Determining whether weight status mediates the association between number of cigarettes smoked per day and all-cause mortality among US adults who smoke cigarettes. - Luis Miguel Mestre; Roger S Zoh; Cydne Perry; Julia Fukuyama; Maria A Parker (PLoS ONE)
Introduction While there is evidence demonstrating the association between cigarette smoking and weight status, and mortality and weight status, it has not been examined whether weight status is a mediator between number of cigarettes smoked per day (CPD) and all-cause mortality, limiting our knowledge of this association and potential novel approaches to reduce all-cause mortality due to cigarette smoking. We aimed to evaluate whether weight status mediated the association between CPD and mortality. Methods We harnessed the 2003-2018 NHANES and the Linkage Mortality Files, which included adults who smoked ≥ 100 lifetime cigarettes (unweighted n = 5,676). A generalized linear model estimated the association between cigarettes smoked per day (CPD) and weight status (e.g., Body Mass Index (BMI) or Waist Circumference (WC)). An Accelerated Failure Time model with a Weibull distribution estimated the association between CPD and all-cause mortality with weight status as a mediator, adjusting for age, SES, alcohol consumption, race/ethnicity, sex/gender, blood pressure, total cholesterol, and physical activity. Results Between 2003-2018, the sample's mean BMI was 27.97 kg/m2, sample's mean WC was 97.58 cm and mean CPD was 13.21. The total effect in the mediation analysis of WC adjusted by BMI levels in the association between CPD and all-cause mortality was -0.44 (95% CI =  -2.00, -0.20; p =  0.016), the average direct effect was -0.35 (95% CI =  -1.86, -0.10; p =  0.036), and the average indirect effect was -0.10 (95% CI =  -0.23, -0.05; p < 0.001). Conclusion WC, as a surrogate measure of weight status, when adjusted by BMI levels, was a partial mediator between CPD and all-cause mortality. Public health interventions aimed to reduce mortality due to cigarette smoking at the population level should consider weight management programs as a harm reduction strategy to reduce mortality.